Financial-Law Problems in Providing Free-of-Charge Legal Aid in Poland. Legal Comparative Aspects - Świstak, Marzena (Review of European and Comparative Law, 2021)
Free-of-charge legal assistance remains one of the key areas of state activity. However, the system created is not optimal and its formal, organisational and financial framework needs to be modified. This concerns not only an increase in the amounts of funding, but also the quality of services provided. Not only is the choice of the legal and organisational model of providing legal assistance doubtful, but also the subjective and objective scope of the statutory regulations (including in the context of interpretation of tax regulations) raise some objections. As a postulate for the law as it should stand de lege ferenda), it is proposed to make appropriate legislative changes, aimed not only at clarifying the content of the provisions, or removing the legislative inconsistencies found, but also at thoroughly considering a remodelling of the legal assistance system in Poland. The above conclusions were formulated against the backdrop of the organisational and financial legal solutions adopted in other countries. To this end, the author used the formal-dogmatic and comparative legal methods, and also resorted to the historical method as an auxiliary method, in order to show the evolution of the institution under analysis.